2019
DOI: 10.1186/s12864-019-6391-9
|View full text |Cite
|
Sign up to set email alerts
|

Different transcriptional response between susceptible and resistant common carp (Cyprinus carpio) fish hints on the mechanism of CyHV-3 disease resistance

Abstract: BackgroundInfectious disease outbreaks form major setbacks to aquaculture production and to further development of this important sector. Cyprinid herpes virus-3 (CyHV-3) is a dsDNA virus widely hampering production of common carp (Cyprinus carpio), one of the most farmed fish species worldwide. Genetically disease resistant strains are highly sought after as a sustainable solution to this problem. To study the genetic basis and cellular pathways underlying disease resistance, RNA-Seq was used to characterize … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 67 publications
3
15
0
Order By: Relevance
“…These findings were in line with TRIMs, which were found regulated in the survivors of breeding strain for group A and in the healthy control of non-breeding strain for group B. The above finding of TRIM is coincident with one of recent revealed CyHV-3 resistant related DEGs with identified QTLs (13). In the survivors from the breeding strain, the higher PI3K also suggests higher autophagy, since the PI3K/AKT/mTOR pathway enhances this process (48).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings were in line with TRIMs, which were found regulated in the survivors of breeding strain for group A and in the healthy control of non-breeding strain for group B. The above finding of TRIM is coincident with one of recent revealed CyHV-3 resistant related DEGs with identified QTLs (13). In the survivors from the breeding strain, the higher PI3K also suggests higher autophagy, since the PI3K/AKT/mTOR pathway enhances this process (48).…”
Section: Discussionsupporting
confidence: 85%
“…The first transcriptional analysis of carp anterior kidney mainly pointed out the important role of humoral immune responses, especially those related to immunoglobulin (1). Spleen transcriptomic analyses comparing the susceptible and resistant common carp revealed that the susceptible fish elicited a typical anti-viral interferon response, while the upregulated IL-8 attracted innate immune cells and related response may play an essential role in resistant fish (13).…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent focus was to reveal differences in the immune response among strains of common carp with incomparable sensitivity to viral infection. After using an RNA sequencing method, followed by transcriptome analysis of differentially expressed genes, it was found that susceptible fish responded to CyHV-3 infection with production of IFNs and ISGs more quickly than resistant ones (Tadmor-Levi et al, 2019). In another study, Adamek, Matras, et al (2019) (Adamek, Oschilewski, et al, 2017).…”
Section: Immune Re S P On S E On Ce Vmentioning
confidence: 99%
“…The previous studies showed that fish exhibit higher individual variations in response to pathogen infection (28)(29)(30). Genetic factors that favor the survival of asymptomatic individuals could be used as targets for selecting disease-resistant fish, thus reducing economic loss from infectious disease (31). Although accumulating studies have been focused on generating disease (or stress)-resistant fish strains, the mechanisms remain largely unknown (31,32).…”
Section: Introductionmentioning
confidence: 99%